Integration of ChatGPT in High School Chemistry Education: An Exploratory Study on the Use of AI by Teachers and Students - Catur Fathonah Djarwo; Alex Agustinus Lepa (PT. Hasba Edukasi Mandiri, 2025)
The rapid development of artificial intelligence technology has opened new opportunities for transforming learning in various disciplines, including chemistry. Given the urgency of increasing digital literacy and the need for adaptive learning resources, the utilization of ChatGPT as a learning tool at the high school level is an important topic to examine. This study explores how teachers and students use ChatGPT in the chemistry learning process, identifying the benefits, challenges, and pedagogical applications of its use. An exploratory qualitative case study design was used, involving two teachers and ten students. Data were collected through semi-structured interviews, observation, and documentation and analyzed thematically. The results showed that ChatGPT was used as a partner for clarifying concepts, a tool for preparing questions, and a medium for reflecting on learning. However, optimal use was limited by students' low skill level in composing appropriate prompts and teachers' limited ability to validate information from AI. This study concludes that integrating ChatGPT into chemistry education positively impacts concept understanding and independent learning but requires pedagogical intervention, such as AI literacy training and developing critical and reflective learning strategies. This study contributes to the theoretical development of AI integration in science education, offering practical recommendations for developing teacher and student competencies in effectively and responsibly utilizing technology.